2013
DOI: 10.1186/1471-2164-14-908
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan for signatures of differential artificial selection in ten cattle breeds

Abstract: BackgroundSince the times of domestication, cattle have been continually shaped by the influence of humans. Relatively recent history, including breed formation and the still enduring enormous improvement of economically important traits, is expected to have left distinctive footprints of selection within the genome. The purpose of this study was to map genome-wide selection signatures in ten cattle breeds and thus improve the understanding of the genome response to strong artificial selection and support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 81 publications
(117 reference statements)
9
100
3
Order By: Relevance
“…Additionally, we provide evidence that the p.F279Y variant similarly affects milk production traits in FV, corroborating its presumed causal role. The p.F279Y variant has likely been a target of recent selection for protein content because the frequency of the PP-enhancing (i.e., phenylalanine-encoding) allele increased in both FV and HF, which agrees with selection signature analyses in several cattle breeds (Hayes et al, 2009;Rothammer et al, 2013).…”
Section: Short Communicationsupporting
confidence: 62%
“…Additionally, we provide evidence that the p.F279Y variant similarly affects milk production traits in FV, corroborating its presumed causal role. The p.F279Y variant has likely been a target of recent selection for protein content because the frequency of the PP-enhancing (i.e., phenylalanine-encoding) allele increased in both FV and HF, which agrees with selection signature analyses in several cattle breeds (Hayes et al, 2009;Rothammer et al, 2013).…”
Section: Short Communicationsupporting
confidence: 62%
“…Finally, there is a very strong signature of selection on BTA11 for the BP population, where the closest gene to the maximum signal is BMP10 ( bone morphogenetic protein 10 ). Within this genomic region on BTA11, some authors [46, 47] identified signatures of selection and several genes that could be associated with fertility: PROKR1 ( prokineticin receptor 1 ), GFPT1 ( glutamine - fructose - 6 - phosphate transaminase 1 ), GMCL1 ( germ cell - less spermatogenesis associated 1 ), PCBP1 ( poly ( rC ) binding protein 1 ) and EHD3 ( EH - domain containing 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations also elucidated that MAP2K6 was associated with various economic traits in livestock, some of which are related to bone development. A genomewide scan for selection signatures in ten cattle breeds revealed that MAP2K6 is associated with carcass weight, back fat and marbling in Korean beef cattle (Rothammer, Seichter, Förster, & Medugorac, ). Furthermore, MAP2K6 participates in the gonadotropin signalling pathway, which has been identified to be associated with divergent growth traits according to a multiomics analysis in an F 2 Charolais × Holstein population (Widmann et al., ).…”
Section: Discussionmentioning
confidence: 99%